Construction of Regional Input-Output Tables in Finland 2002 - Mikko Koutaniemi; Tuomas Louhela (European Regional Science Association (ERSA), 2006)
The aim of this paper is to describe, how supply and use tables and symmetrical input-output tables are made for Finnish regions. Analysis was done first time for the year 1995. Studies made in 1995 and 2002 are not totally comparable, because of methodological modifications at the national accounts. Goal of the project is, however, to enable studies analysing changes in the regional economic structures. Research results make possible to analyse one region at the time or to do comparisons among regions simultaneously. Tables include information about consumption, investments, exports and imports, production value and volume of goods and services, and economical interdependies of the regions and industries. Corner stone of national as well as regional accounts is a European System of National Accounts ESA 1995. In the supply and use tables national accounts are balanced and divided to the products, which reduces statistical discrepancy. The biggest difference between studies of 1995 and 2002 is the way, how trade flows are estimated. There are no survey made to the industrial establishments in the current research. Trade flows are estimated instead by freight flow approach, which combines industrial products' sales and transportation data. First regional balances of supply and demand have now been estimated. From the economical transactions, private consumption and exports and imports, are already divided to the National Accounts product classification level. Research continues now by dividing reminding parts of the regional balance of supply and demand to the products and by fixing problematic parts of it, such as production taxes and subsidies, foreign trade and interregional trade flows. When regional balances of supply and demand are almost equal, product dividing will be finished and making of supply and use tables will begin. In addition to supply and use tables there is a need of data from amount and hours of labour by industry. Data from the labor is from Regional Accounts and labor hours will be estimated as a new economic transaction by using information from Regional Accounts and service structure statistics.
Keywords: 330